Inflationare Deflation oder die Dominanz der globalen Finanzmärkte - Altvater, Elmar (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2004)
The price deflation of goods is accompanied by an increase in the "price" of capital, the rate of interest in real terms. High real rates of interest are the consequences of the sharp competition of currencies. The outcome is a special kind of "financial repression", oppressing accumulation and growth. If real interest rates are higher than the real rates of growth, debtor nations come in structural problems. So the debt crisis of the eighties and the finance crisis of the nineties indicate a new post-modern capitalist regime of "plundering".